PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE GIVING QUESTIONS AND GETTING ANSWERS DISERTAI HANDOUT TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMP NEGERI 5 SAWAHLUNTO - mawita, Des; Anggraini, Villia; Cesaria, Anna (STKIP PGRI Sumbar, 2014)
ABSTRACTThis research was background by the students respond to questions given teachers and less motivated to ask the teacher. The research hypothesis is that students understanding of mathematical concepts apply Active Learning Strategies Giving Type Questions and Getting Answers Accompanied Handout better understanding of the mathematical concepts that students applying conventional learning. This research is to design experimental with Random subject. Instrument used is in the form of an essay test to test the reliability of Â R11 = 0.92. Based on the analysis of data known to both classes of normally distributed samples, homogeneous and tcount = 1.71 is greater than ttable = 1.67 then the hypothesis is accepted. Thus, it can be concluded that the students understanding of mathematical concepts that use Type Active Learning Strategies Giving and Getting Answers Questions Accompanied Handout than better understanding of the mathematical concepts students to apply classroom learning conventional in the class VIII SMP N 5 Sawahlunto.